Path Tracking of Mobile Robot in Crops: Performance Evaluations of Position Control - Muñoz-Gamboa, J; Urrea-Onate, E (Kluwer Academic Publishers, 2015)
Evaluation of the performance of three controllers: adaptive PID, model reference adaptive controller, and fuzzy controller, is presented, applied to a mobile robot for autonomous path tracking in a crop. Different tests are run in a simulation environment in order to compare the same trajectory performed under each of those controllers. The tests are designed and implemented using Simulink® programming tools, making the robot follow a desired path across the crop. The results are compared considering the different error indices, curves and actuator requirements of each controller, in order to arrange them in different categories. © 2013, Springer Science+Business Media Dordrecht.